2022
DOI: 10.3389/feart.2022.931012
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Phases Fluid Activity Characteristics of Longmaxi Formation and Its Impact on Resistivity in the Changning Area, Southern Sichuan Basin, Southwest China

Abstract: Wells with low gas content and low resistivity in the Changning area, southern Sichuan Basin were selected for this study. The burial-thermal history was reconstructed and the characteristics of multi-phase fluid activity were clarified using microscopic observation and testing of fluid inclusions in the Longmaxi shale fracture veins. Compared with wells with a high gas content and high resistivity, the influence of fluid activity on resistivity was analyzed. The results showed that the thermal evolution of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…The strong fracturing action of large faults has a significant effect on the preservation conditions of shale gas, because a strong structural deformation leads to the development of fractures in shale gas reservoirs, roofs, and floors, resulting in the compression stress concentration of the footers of individual reverse faults. Fracture systems and fissures can lead to shale gas escape, severe gas-bearing damage, and possible freshwater leaching . It was also revealed that shale gas wells with ultralow resistivity have poor preservation conditions, and the formation water enters the fault plane and nearby fissure system, resulting in a decrease in the shale gas bearing.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong fracturing action of large faults has a significant effect on the preservation conditions of shale gas, because a strong structural deformation leads to the development of fractures in shale gas reservoirs, roofs, and floors, resulting in the compression stress concentration of the footers of individual reverse faults. Fracture systems and fissures can lead to shale gas escape, severe gas-bearing damage, and possible freshwater leaching . It was also revealed that shale gas wells with ultralow resistivity have poor preservation conditions, and the formation water enters the fault plane and nearby fissure system, resulting in a decrease in the shale gas bearing.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Fracture systems and fissures can lead to shale gas escape, severe gas-bearing damage, and possible freshwater leaching. 46 It was also revealed that shale gas wells with ultralow resistivity have poor preservation conditions, and the formation water enters the fault plane and nearby fissure system, resulting in a decrease in the shale gas bearing. The overall burial depths of the low-and normalresistivity wells were relatively shallow, and the burial depth of the normal resistivity wells was generally below 3000 m. Only a few small-and medium-sized faults developed near the lowand normal-resistivity shale gas reservoirs, and the later transformation was relatively weak, with good overall preservation conditions (Figure 9c,e).…”
Section: Analyses Of Gas Content Differences and Factors Among Differ...mentioning
confidence: 99%